Application of Buddhadhamma principles to increase efficiency in the performance of land officers in Yasothon Province - Panlert, Korakrot; ผศ.ดร., พระครูสุตวรธรรมกิจ; พันธไชย, ผศ.ดร.สยามพร (RATANABUTH JOURNAL, 2022)
The objectives of this research were 1) to study the level of application of Buddhist principles to increase the efficiency in the performance of land office officers in Muang District, Yasothon Province. 2) to study the relationship between the Sangkhahavutdhamma principles and the application of Buddhadhamma principles to increase the efficiency of the performance of land office officers in Muang District, Yasothon Province. and 3) to suggest an integrated application of Buddhist principles to increase the efficiency in the performance of the staff of the Land Office in Muang District, Yasothon Province. There was quantitative research consisting of 90 officers from the Land Office of Mueang District, Pa Tio District and Sai Mun District, Yasothon Province. The tool was a questionnaire, while the qualitative research. There were 9 groups of key informants. The tool was an interview form. The results showed that. The level of application of Buddhadhamma principles to increase the efficiency in the performance of officials of the Land Office, Yasothon Province, as a whole, was at a high level. The mean was 3.52. When considering each aspect, it was found that the Piyawaja side had an average of 3.62. The mean was at the level of 3.55. The resistive had the mean at the level of 3.51. With an average of 3.42. Integrating the work of land officials to increase work efficiency under the management principles of Edwards Deming as a whole at a high level The average was 3.50 when considering each side found that Planning 3.52 Improvement 3.51 Operation 3.43 Audit 3.42. The relationship between Sangahavatthuthamma principles to increase the efficiency of the performance of land office officials in Muang District, Yasothon Province was be at a high level of 0.741**. Suggestions for the application of Buddhadhamma principles to increase the efficiency in the performance of staff of the Land Office, Yasothon Province. It was found that the donation of items and making merit regularly when there is merit or tradition that occurs in offices and communities in order to help and share with others who are in trouble and need help. Officers to speak sweetly, do not speak rudely.